INTERPERSONAL COMMUNICATION BETWEEN OPINION LEADER AND MINORITY GROUP ON SOCIAL HARMONY IN SOUTH SULAWESI - Bahfiarti, Tuti; Arianto, Arianto; Fatimah, Jeanny Maria (ISJN Journal, 2019)
Abstrak Interpersonal communication involves the exchange of verbal and non-verbal messages that can directly affect the sender and recipient of the message. The context of interpersonal communication can be applied to opinion leaders and minority groups in direct interaction. Relationship between opinion leaders and minority groups have differences in religion, beliefs, culture, and customs can be applied through open interpersonal communication, empathy, and equality. The goal is to maximize the role and opinion leader function of the majority group, namely the Toraja ethnic group in interacting with the Bugis ethnic minority group of Makassar for social harmonization in a multicultural and multiethnic society. The research method approaches the constructivism paradigm. Methods of data collection through Focuss Group Discussion, observation, and in-depth interviews. Furthermore, the data collected in the analysis uses a qualitative approach to generalize the conclusions of the results of data analysis inductively. Informants were determined through purposive sampling based on high opinion leader interaction levels with individuals or groups outside their ethnicity, with the aim that the informants interviewed had a wealth of insight and extensive knowledge about ethnic opponents, and had experience of associating with individuals or groups outside their ethnicity. 3 informants were chosen in Toraja Regency and 3 in Makassar City, and 7 Bugis Ethnic Makassar who interacted directly with opinion leaders and the community in the majority group. The results of the study found that interpersonal communication was carried out by open opinion leaders, empathy, and equal attitudes. Opinion leader applies the concept of interpersonal communication with minority groups through interpersonal communication skills, such as the ability to imitate, identification skills, and the ability of sympathy with minority groups dominated by ethnic Bugis Makassar and the majority group dominated by ethnic Toraja. The obstacle factor of interpersonal communication between opinion leaders and minority groups is first, barriers to the status effect, perceptual distorsion barriers, and barriers to cultural differences on minority groups that have different cultures, religions and social environments.